Identification of quantitative trait loci (QTL) controlling fibre content of sugarcane (Saccharum hybrids spp.). (19th March 2021) - Islam, Md S.; Pan, Yong‐Bao; Lomax, Lionel; Grisham, Michael P.
Abstract: The fibre content (FC) of sugarcane millable stalks is important for both sugar and bioenergy production. Higher FC favours the energy producer while lower FC facilitates the efficient sugar extraction. A molecular marker for FC helps select improved sugarcane cultivars with favourable partitioning of FC for both sugar and energy production industries. A quantitative trait loci (QTL) study was conducted using an enriched linkage map of LCP 85‐384 and FC data from two crop cycles (plant cane and first ratoon) of its self‐progeny population. A total of five unique QTL were identified across both crop cycles and combined, of which three QTL ( qFC020, qFC044 and qFC053 ) were common explained a total of 22.46%, 23.93% and 25.14% of the phenotypic variances for plant cane, first ratoon and combined data, respectively. As FC values increased gradually, the QTL allele combination effect also increased. Using markers linked to these putative common QTL alleles would benefit the breeders to select sugarcane lines for sugar and bioenergy production.